Island Latissimus Dorsi Muscle Flap and a Perforator Flap in Repairing Post-Gunshot Thoracic Spine CSF Fistula: Case Presentation - Nangole F. Wanjala; Khainga Ominde Stanley (Case Reports in Surgery)
Persistent posttraumatic CSF fluid leakage may present a challenge to manage. Failure to address the leakage may result in complications such as meningitis, septicemia, radiculopathy, muscle weakness, and back pains. While the majority of the leakages may be managed conservatively, large dura defects as a result of gunshot wounds or motor vehicle accidents are best managed by surgical interventions. This may range from primary closure of the defect to fascial grafts, adhesive glues, and flaps. We present our experience with the use of flaps in a patient who had sustained such wounds in the thoracic spine. An island latissimus dorsal flap and a perforator fasciocutaneous flap were used to close the defect. Postoperatively the patient recovered well and the wounds healed without any complications.